Neonatal nurses' response to a hypothetical premature birth situation: What if it was my baby?. (November 2018) - Green, Janet; Darbyshire, Philip; Adams, Anne; Jackson, Debra
Background: Evolving technology and scientific advancement have increased the chances of survival of the extremely premature baby; however, such survival can be associated with some severe long-term morbidities. Research question: The research investigates the caregiving and ethical dilemmas faced by neonatal nurses when caring for extremely premature babies (defined as ≤24 weeks' gestation). This article explores the issues arising for neonatal nurses when they considered the philosophical question of 'what if it was me and my baby', or what they believed they would do in the hypothetical situation of going into premature labour and delivering an extremely premature baby. Participants: Data were collected via a questionnaire to Australian neonatal nurses and semi-structured interviews with 24 neonatal nurses in New South Wales, Australia. Ethical considerations: Relevant ethical approvals have been obtained by the researchers. Findings: A qualitative approach was used to analyse the data. The theme 'imagined futures' was generated which comprised three sub-themes: 'choice is important', 'not subjecting their own baby to treatment' and 'nurses and outcome predictions'. The results offer an important and unique understanding into the perceptions of nursing staff who care for extremely premature babies and their family, see them go home and witness their evolving outcomes. The results show that previous clinical and personal experiences led the nurses in the study to choose to have the belief that if in a similar situation, they would choose not to have their own baby resuscitated and subjected to the very treatment that they provide to other babies. Conclusion: The theme 'imagined futures' offers an overall understanding of how neonatal nurses imagine what the life of the extremely premature baby and his or her family will be like after discharge from neonatal intensive care. The nurses' past experience has led them to believe that they would not want this life for themselves and their baby, if they were to deliver at 24 weeks' gestation or less.